The political theology of Catholic conservatism in contemporary Peru - Casey-Pariseault, Matthew (2022)
Since the 1980s, Peru has witnessed a resurgence of Catholic conservatism. By analyzing the actions and ideologies of the Catholic right through the press and in Church documents, this article explains the unification of conservative Catholics via a mixture of: 1) an anti-leftist response to liberation theology, and 2) a rejection of the growing influence of feminism and the LGBTQ rights movement. Gradually, laypeople and the conservative clergy turned to conservative evangelicals as important allies in the fight against the alleged evils of abortion, leftist economics, and «gender ideology». This paper joins the literature on religious diversity in Peru and Latin America to show that while Catholic conservatism has experienced some setbacks, it remains strong even in the era of Pope Francis.